Technological change of organizations at the digital level and its impact on the future of competencies and jobs : A survey of a group of research and studies - Cherifi, Sofiane; Bachir, Ameur (Journal of Human Sciences, 2022)
This paper aims to alert to the impact of new technological changes in the field of digital transformation on the business world, and the consequent needs of new competencies and jobs, which will expand the scope of development and change and the occurrence of unprecedented transformations in the economy, labor market and industrial sector, where digital transformation represents one of the The most important drivers and catalysts for growth in the world today, and to discuss how these transformations will affect the business and jobs sectors in the future, we address the most prominent of these digital transformations, their features and size, citing a number of studies and research, including: The Economist Intelligence Unit study and surveys by Mckinzy Institute, huffingtonpost and others.., where It concluded: 1- The necessity of developing human skills and competencies and qualifying resources in line with digital transformation 2- The inevitability of cultural change for organizations and the adoption of flexibility to face the digital wave. 3- Increasing dependence on data and digital inclusion.